DAMPAK PELATIHAN GURU PEMANDU BIDANG STUDI IPA TERHADAP PEMBELAJARAN IPA DI SEKOLAH DASAR - Hindarto, Nathan (Pendidikan Dasar, 2009)
ABSTRACT: The aim of this research was to acknowledge, (1) the effect of the Science Guide Teacher training towards the elementary school’s science teacher performance and (2) the effect of the training to the student’s science learning results. To identify these effects, the tools used were a questionnaire, and documents from the Elementary School’s Science Guide Teacher and also from the Pati Regent’s Head of Elementary Education Office. The research design used for this research was ex-post facto, and it was described using percentage. The research results shows that the Elementary School’s Science Guide Teacher training gave significant effect on the science learning at Public Elementary School in the Pati Regent, both on the teacher’s performance and  also the student’s learning results.